School absenteeism among students in Germany, Japan, Sweden, and the United Kingdom:: A comparative study using PISA data - Fredriksson, Ulf; Rasmusson, Maria; Backlund, Åsa; Isaksson, Joakim; Kreitz-Sandberg, Susanne (Nordic Journal of Comparative and International Education (NJCIE), 2023)
School absenteeism is a challenge in many countries. Still, there are few comparisons between countries, which is partly due to a lack of shared definitions of concepts. This article makes use of PISA data to compare self-reported student absenteeism in Germany, Japan, Sweden, and the United Kingdom (UK). Three data sets are used, from 2012, 2015, and 2018. The self-reported absenteeism, which is referred to as truancy in the PISA studies, was measured as having skipped a whole school day at least once in the two full weeks before students completed the PISA student questionnaire. The results show great variation between the studied countries, from 24.4% in the UK in 2015 to 1.5% in Japan in 2012. The percentage of students who reported having skipped school is much higher in the UK than in the other three countries. The differences between the countries concerning the percentage of students reporting having been absent from school are significant for all years, except between Sweden and Germany in 2015. Germany and the UK have a similar pattern in development, with the highest percentages in 2015, while Sweden and Japan have small (albeit not significant) increases from 2012 to 2018. The UK is the only country where the changes between 2012 and 2015 as well as between 2015 and 2018 were significant. It is not possible to see any obvious patterns between the countries that might be linked to differences related to their welfare regimes, education systems, or values. To find such patterns, it may be necessary either to include more countries in a study or to conduct more in-depth studies on each country.